Assistance in Strengthening Village Governance Through the Development of Standard Operating Procedures (SOP) and Increasing the Capacity of Villages Apparatus: Community Service in Sungai Arang Hamlet, Jambi, Indonesia - Albadry, Syah Amin; Darmawanto; Rusnaini, Sasmita; Pratiwi, Widya; Hamirul, Hamirul (Indonesian Community Empowerment Journal, 2024)
Effective village governance is an important foundation for sustainable development at the local level. However, many villages in Indonesia, including Sungai Arang Hamlet in Jambi, still face challenges in terms of governance, which can be seen from weak administrative systems, lack of transparency, and low capacity of village officials. This research uses a participatory community service approach which involves a series of activities, including: (1) Identifying village problems and needs through focus group discussions (FGD) and in-depth interviews; (2) Development of standard operating procedures (SOP) for various aspects of village administration; (3) Training and capacity building for village officials regarding SOP implementation; (4) Assistance and monitoring of SOP implementation; and (5) Evaluation of program impact. The research results show a significant improvement in village governance after program implementation. The developed SOPs have helped improve the efficiency and effectiveness of public services, increase transparency and accountability, and strengthen public participation in decision-making. In addition, the capacity of village officials has also increased, reflected in a better understanding of their duties and responsibilities, as well as a better ability to carry out administrative tasks. In conclusion, this community service program has made a positive contribution in strengthening village governance in Sungai Arang Hamlet. Developing SOPs and increasing the capacity of village officials has proven effective in improving the quality of public service s, transparency, and accountability. This research recommends that this community service model can be replicated in other villages that have similar problems.